EMPIRICAL STUDY OF LAND ACQUISITION IN PENINSULAR MALAYSIA: ACHIEVING EQUILIBRIUM ON COMPETING PUBLIC AND PRIVATE INTERESTS (UUM Journal of Legal Studies, 2024)
The right to own property is an intrinsic human right that grants ownership and enjoyment to owners. The property right, however,is not absolute because it is subject to the state’s authority to compulsorily acquire land that is in private hands, which is referredto as land acquisition. Land acquisition refers to the power granted to the state government to obtain privately owned land for a publicpurpose, in exchange for fair compensation (Keith et al., 2008). Land acquisition is an essential strategy for the state to address the limited availability of land when it is necessary to create railways, airports, or any other infrastructure for the benefit of the public (Jonathan, 2012). Nevertheless, the process of acquiring land is a lengthy procedure that has a significant influence on the local community. This is because it involves conflicting interests between the government that is seemingly acting on behalf of the general public, and the very public who are affected by the acquisition itself. Therefore, the land acquisition system is supposed to be designed as a method of reconciling these conflicting interests. Despite this ideal purpose, numerous countries, particularly in emerging nations like Malaysia, face challenges in achieving a harmonious equilibrium between the conflicting public and private interests. These challenges arise from inadequate legislative safeguards and a conventional hierarchical approach adopted by the government branches of the state (Ghimire et al., 2017). The public aspect is usually legally defined, but private perspectives may not always be apparent. In order to achieve the right balance between conflicting public and private interests, this study aims to examine the perspectives of the individuals, i.e., the landowners who are directly affected by the land acquisition. This study examines their perceptions and attitudes towards the whole process and procedures of the land acquisition to which they were subjected, as well as their corresponding responses and willingness to make sacrifices in pursuit of the higher objectives of the state. To achieve this goal, a questionnaire survey has been used as the methodology of collecting data from the landowners and the results are presented using descriptive analysis. The outcome demonstrated that whenever the state exercises the power of land acquisition, the balance tends to side with the interest of the public rather than the private interests of the affected individuals, both in law and in practice. In addition, Malaysia became a member of the United Nations on 17 September 1957. Hence, it is crucial to examine the principles of compulsory land acquisition as delineated by the United Nations study (Keith et al., 2008). The final section of this article provides an analysis of the findings and then make recommendations by referring to Australia’s best practices for adoption in Peninsular Malaysia. The methodologies employed in this study are the data collection method and comparative legal analysis.